2006
DOI: 10.1891/rtnp.20.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Having a Sibling With Schizophrenia: A Phenomenological Study

Abstract: Limited attention has been paid to experiences of individuals with siblings diagnosed with schizophrenia. The purpose of this article is to address this gap by exploring the impact of having a brother or sister with schizophrenia. The lived experience of 6 individuals with a sibling with schizophrenia was explored using van Manen's (1997) Hermeneutic Phenomenology. Four themes were identified: struggling to understand, struggling with the system, caring for the sibling, and seeing beyond the illness. Health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 31 publications
16
39
0
Order By: Relevance
“…In an effort to alleviate conflict within the family and facilitate productive discussions, siblings indicated that they often played the role of mediator in their family. The finding gleaned from the interviews regarding the conflicting familial responses to AN is consistent with other studies on siblings of individuals with other severe mental illnesses such as schizophrenia (Barnable, Gaudine, Bennett, & Meadus, 2006;Jewell & Stein, 2002). Given that AN is a complex psychiatric illness that is often accompanied by medical complications, it is perhaps understandable that this illness engenders a multitude of emotional responses from family members.…”
Section: Discussionsupporting
confidence: 86%
“…In an effort to alleviate conflict within the family and facilitate productive discussions, siblings indicated that they often played the role of mediator in their family. The finding gleaned from the interviews regarding the conflicting familial responses to AN is consistent with other studies on siblings of individuals with other severe mental illnesses such as schizophrenia (Barnable, Gaudine, Bennett, & Meadus, 2006;Jewell & Stein, 2002). Given that AN is a complex psychiatric illness that is often accompanied by medical complications, it is perhaps understandable that this illness engenders a multitude of emotional responses from family members.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the potentially traumatic impact of schizophrenia, recent research has found that family members also report beneficial or positive elements of their experience, such as personal growth (Barnable, Gaudine, Bennett, & Meadus, 2006;Chen & Greenberg, 2004;McKenzie, 2000;Morton et al, 2013;Wiens & Daniluk, 2009). The current study aimed to explore firstly, whether these family members experience posttraumatic growth and secondly, how personality traits (e.g., extraversion), social support, and emotional or instrumental coping strategies influence the development of this growth.…”
Section: Introductionmentioning
confidence: 99%
“…The current study aimed to explore firstly, whether these family members experience posttraumatic growth and secondly, how personality traits (e.g., extraversion), social support, and emotional or instrumental coping strategies influence the development of this growth. Understanding the experience and development of personal growth will help mental health professionals to better support families in the challenges they face, whilst Several qualitative studies have reported the benefits experienced by family members of living with an individual diagnosed with schizophrenia, including personal growth, greater tolerance and compassion, stronger family relationships, and the illness providing meaning to their life (Barnable et al, 2006;Chen & Greenberg, 2004;McKenzie, 2000;Morton et al, 2013;Wiens & Daniluk, 2009). Tedeschi and Calhoun's (1996) model of Posttraumatic Growth (PTG) offers a useful framework to understand the positive outcomes that these family members described as resulting from their stressful and at times traumatic experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The affected sibling's psychiatric problems, such as social isolation, lack of motivation (Friedrich, Lively, & Buckwalter, 1999), hallucinations, and delusions (Barnable, Gaudine, Bennett, & Meadus, 2006;Friedrich et al, 1999), also seem to strongly affect the healthy sibling's subjective burden (Greenberg, Kim, & Greenley, 1997) and psychological wellbeing (Mailick Seltzer et al, 1997). The first onset of the illness is associated with feelings of being overwhelmed by the psychological impact on the affected sibling and the subsequent impact on their own lives (Sin, Moone, & Harris, 2008).…”
mentioning
confidence: 99%